Assessing the Growth Performance of Nursing Trees (Pongamia pinnata) at Takasago-UNIMAS Educational Forest - Mohammad Aizuddin Fahmi, Abdul Rafar @ Abdul Ghafar (Universiti Malaysia Sarawak, (UNIMAS), 2022)
Land degradation has worsened in recent decades, posing new challenges, particularly for living organisms in the ecosystem. Land restoration can be accomplished using proper approaches to recover degraded land caused by human activities such as development and construction. An assessment was conducted to study the survival rate and growth performance of planted Pongamia pinnata trees as the nursing tree at Takasago-UNIMAS Educational Forest. In this study, the degraded post-construction areas planted with Pongamia pinnata through the box planting method were selected. The study plot had been delineated into three (3) study plots (Plot A with spacing of 5m x 5m, Plot B with spacing of 2.5m x 2.5m and Plot C planted with spacing of 3m x 3m) with 6 smaller subplots within each plot. The survival rate and growth performance in terms of height and stem diameter of planted trees were assessed in all plots. The results showed that the survival rate of planted trees in plot A, B and C were at 62%, 25% and 53%, respectively. The results for growth performance showed that the mean of tree height in plot A (216.76 cm) was significantly higher than in plot B (192.42 cm) and plot C (121.46 cm). Additionally, the mean stem diameter recorded for plot A, B and C were 5.05 cm, 3.88 cm, and 1.79 cm, respectively. Mean annual increment in height (MAIH) and diameter (MAID) of planted P. pinnata in Plot C were significantly higher than in both plots A and B. The high survival rate and substantial growth performance of P. pinnata indicated that soil conditions and properties along with other limiting factors have affected the survival rate and growth performance of planted P. pinnata